2012
DOI: 10.3402/iee.v2i0.17093
|View full text |Cite
|
Sign up to set email alerts
|

Rodents on pig and chicken farms – a potential threat to human and animal health

Abstract: Rodents can cause major problems through spreading various diseases to animals and humans. The two main species of rodents most commonly found on farms around the world are the house mouse (Mus musculus) and the brown rat (Rattus norvegicus). Both species are omnivorous and can breed year-round under favourable conditions. This review describes the occurrence of pathogens in rodents on specialist pig and chicken farms, which are usually closed units with a high level of bio-security. However, wild rodents may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 96 publications
2
52
0
1
Order By: Relevance
“…They can serve as natural reservoirs or mechanical vectors for several bacterial and viral pathogens, including various picornaviruses such as enteroviruses and ECMV, which are known to infect humans, pigs, and other animal species (21,22). Results showing that mice can carry viable SVA (small intestine and feces) and that flies can carry the virus' nucleic acid suggest that these species may play a role in SVA ecology.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…They can serve as natural reservoirs or mechanical vectors for several bacterial and viral pathogens, including various picornaviruses such as enteroviruses and ECMV, which are known to infect humans, pigs, and other animal species (21,22). Results showing that mice can carry viable SVA (small intestine and feces) and that flies can carry the virus' nucleic acid suggest that these species may play a role in SVA ecology.…”
Section: Figmentioning
confidence: 98%
“…Mice and houseflies are among the most common and widely distributed pests and have been frequently associated with infectious disease transmission to humans and animals (21,22,27). They can serve as natural reservoirs or mechanical vectors for several bacterial and viral pathogens, including various picornaviruses such as enteroviruses and ECMV, which are known to infect humans, pigs, and other animal species (21,22).…”
Section: Figmentioning
confidence: 99%
“…Rodents are known to carry pathogens that may be a risk for public health [14]. Despite this, little is known about the prevalence and geographical distribution of zoonotic rodent-borne pathogens in the Dutch rodent population.…”
Section: Introductionmentioning
confidence: 99%
“…The other evident was rodents entered to sed. Backhans and Fellstrom (2012) argued that rodents on farms pose a danger of introducing new infections into the livestock inside, so rodent control should be considered an important measure to provide good bio-security. Table 2 showed that overall, total farm biosecurity status score (FBSS) was 123.71.…”
Section: Farm Biosecurity Status Score (Fbss)mentioning
confidence: 99%